History of Universities Volume XXXIV/1: A Global History of Research Education: Disciplines, Institutions, and Nations, 1840-1950 - Ku, Ming Chang; Rocke, Alan (History of Universities, 2021)
This book's chapters contain a mix of analysis and discussion looking in depth at the history of higher education. This text presents a global history of research education in the nineteenth and twentieth centuries. Chapters cover topics such as how disciplines are formed and research training, the rise of academic laboratory science, research mathematicians circa 1900 and research training in the humanities in British universities from 1870 to 1939. Other subjects include training language scholars between 1920 and 1940, training researchers in Ibero-Amerca, inventing laboratory science in Meiji Japan, and Chinese physics researchers in the period 1927-1941. The book includes an introduction and conclusion by Kevin Chang and Alan Rocke.